Discriminatory power of the intraoperative cell salvage use in the prediction of platelet and plasma transfusion in patients undergoing cardiac surgery. Issue 2 (October 2015) - Al-Khabori, Murtadha; Al-Riyami, Arwa Z.; Baskaran, Balan; Siddiqi, Mohammad; Al-Sabti, Hilal
Abstract: Introduction: We aim to assess the discrimination of transfused salvaged blood in predicting perioperative platelet and plasma transfusion. Methods: Retrospective review was performed on all patients undergoing cardiac surgery with cell saver (CS) support. The area under the receiver operating characteristics curve was calculated. Results: The discrimination achieved by transfused CS volumes in predicting perioperative platelet and plasma transfusion was poor (AUC 0.642 and 0.613 respectively). None of the covariates included (preoperative platelets, cardiopulmonary bypass use and time, aortic cross clamp time and use of aspirin or clopidogrel within 7 days of surgery) were statistically significant predictors. Conclusion: Volumes of transfused CS blood have poor discrimination in predicting platelet and plasma transfusion.